Interactive Writing / An Advanced Course in Writing Skills: Student's Book - Cook Catherine; Kwan-Terry Anna; Ragan Peter H (Prentice Hall International, 1988)
This book is to train tertiary level students in the skills necessary for effective and coherent writing. Preface, Introduction, To the Teacher, Interaction in the text: the Paragraph, Interaction in the text: the Complete Text, Interaction with the Reader: Meeting the Needs of the Reader, Interaction with the Reader: Presenting a Point of View, Interaction with the Reader: Anticipating the Reader's Response.